The Concept of Social Health From an Iranian Perspective: A Qualitative Exploration - Goli Soofizad; Sakineh Rakhshanderou; Ali Ramezankhani; Mohtasham Ghaffari (Frontiers in Public Health, 2022)
ObjectiveAs one of the health aspects, social health is less well-known than physical and mental aspects. In order to better understand this aspect and considering the importance of social context in its conceptualizing, the present study was performed aiming at explaining the social health and identification of its various aspects in the perspective of Iranian adults.MethodologyThe present study was conducted in 2021 with a qualitative approach and with the participation of Iranian adults and social health professionals. Data were collected through semi-structured interviews with 36 participants who were selected by purposive sampling. The obtained data were analyzed using qualitative (conventional) content analysis and Granheim and Lundman method in the MAXQDA-2020. Guba and Lincoln criteria were observed to evaluate the quality of research results.ResultsUsing data analysis, 3 main categories and 17 subcategories were obtained, including: (1) Conceptual scope of social health (social health as social capital, social health as mental health, social health as moral health), (2) Characteristics of social health (biologic, continual, acquired, evolutionary, relative), and (3) Social health dimensions (openness to interactions, social adaptability, social dutifulness, social self-esteem, mutual trust, communicational capability, social optimism, enjoying social support, public-oriented personality).ConclusionSince social health has a conceptual scope, it is important to try to strengthen and reproduce the dimensions of social health and at the same time use planning, policymaking and appropriate interventions to improve and to promote the dimensions of social health.